“Real‐world” performance of the Confirm Rx™ SharpSense AF detection algorithm: UK Confirm Rx study - Gala, Andre Briosa e; Pope, Michael T. B.; Leo, Milena; Sharp, Alexander J.; Banerjee, Abhirup; Field, Duncan; Thomas, Honey; Balasubramaniam, Richard; Hunter, Ross; Gardner, Roy S.; Wilson, David; Gallagher, Mark M.; et al. (Journal of arrhythmia, 2024)
The novel Confirm Rx™ implantable cardiac monitor (ICM) with SharpSense™ technology incorporates a new P-wave discriminator designed to improve AF detection. This study aimed to evaluate the diagnostic performance of the Confirm Rx™ ICM in detecting AF episodes of varying durations. We conducted a multicenter retrospective analysis of consecutive patients implanted with a Confirm Rx™ ICM (v1.2) across nine UK hospitals, all with documented AF lasting at least 6 min. Electrocardiograms (ECGs) were manually adjudicated by cardiologists. To account for intra- and inter-reviewer variability, a random sample of 10% of ECGs underwent additional review. Disagreements were resolved by a third reviewer. Diagnostic performance was determined by calculating the gross and patient-averaged positive predictive value (PPV) for AF episodes of different duration. The source of false positive (FP) detection was also categorized. Overall, 16,230 individual ECGs from 232 patients were included. The median AF episode duration was 14 min. R-wave amplitude remained stable during follow-up (0.52 ± 0.27 mV [initial] vs. 0.54 ± 0.29 mV [end of follow-up], = .10). The gross and patient-averaged PPV were 75.0% and 67.0%, respectively. Diagnostic performance (gross) increased with progressively longer AF episodes: 88.0% for ≥1 h, 97.3% for 6 h, and 100% for 24 h. The main source of FP during tachycardia was T-wave oversensing (54.2%), while in non-tachycardic episodes it was predominantly ectopy (71.2%). The AF burden precision was excellent (93.3%). The Confirm Rx™ ICM diagnostic performance was modest for all AF episodes (75%), with accuracy increasing for longer AF episodes.